Jane Eyre - Charlotte Brontë (London Vintage Classics, 2016)
As an orphan, Jane's childhood is not an easy one but her independence and strength of character keep her going through the miseries inflicted by cruel relatives and a brutal school. However, her biggest challenge is yet to come. Taking a job as a governess in a house full of secrets, for a passionate man she grows more and more attracted to, ultimately forces Jane to call on all her resources in order to hold on to her beliefs.
Keywords: Classics; Fiction; Romance; Gothic; Historical fiction